2022
DOI: 10.1371/journal.pone.0261868
|View full text |Cite
|
Sign up to set email alerts
|

Interclutch variability in egg characteristics in two species of rail: Is maternal identity encoded in eggshell patterns?

Abstract: Maternal signatures are present in the eggs of some birds, but quantifying interclutch variability within populations remains challenging. Maternal assignment of eggs with distinctive appearances could be used to non-invasively identify renesting females, including hens returning among years, as well as to identify cases of conspecific brood parasitism. We explored whether King Rail (Rallus elegans) eggs with shared maternity could be matched based on eggshell pattern. We used NaturePatternMatch (NPM) software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…Parents of both species share incubation duties, but there may be selection on Common Moorhens to have more highly pigmented eggs for camouflage prior to the start of incubation, or alternatively, for increased individual pattern variability. Both populations exhibited conspecific brood parasitism, but the rate was higher in Common Moorhens, as would be expected at higher breeding density (McRae 1998;Johnson and McRae 2022). We cannot determine the degree to which ecological and social stressors may have contributed to the investment by hens in eggshell pigments, but a comparative analysis of a larger number of species could help shed light on what factors underlie differences between species in the mean degree of eggshell pigmentation.…”
Section: Comparison Of Egg Pigmentation Between Speciesmentioning
confidence: 89%
“…Parents of both species share incubation duties, but there may be selection on Common Moorhens to have more highly pigmented eggs for camouflage prior to the start of incubation, or alternatively, for increased individual pattern variability. Both populations exhibited conspecific brood parasitism, but the rate was higher in Common Moorhens, as would be expected at higher breeding density (McRae 1998;Johnson and McRae 2022). We cannot determine the degree to which ecological and social stressors may have contributed to the investment by hens in eggshell pigments, but a comparative analysis of a larger number of species could help shed light on what factors underlie differences between species in the mean degree of eggshell pigmentation.…”
Section: Comparison Of Egg Pigmentation Between Speciesmentioning
confidence: 89%
“…Recent studies showed that maternal identity can be encoded in egg phenotype (Gómez et al 2021;Šulc et al 2021;Johnson and McRae 2022). Therefore, we expanded our dataset of genetically assigned offspring from 2016 and 2017 by eggs whose phenotypes were measured but could not be genetically assigned to cuckoo females because no DNA was sampled due to early host ejection or predation.…”
Section: Assignment Of Cuckoo Mothers -Egg Phenotype Determinationmentioning
confidence: 99%